The place of utopia in history - Rodrigo-Mendizábal, Iván Fernando (2020)
The article examines the notion of utopia related to history in Ricardo Piglia’s Respiración artificial. While utopia is usually understood as placeless, Piglia suggests a place of strangeness and nostalgia because he makes a discourse on the nature of the novel and its future reader, through a narrative and reflective game in which the plot is about a character who writes to a future time, just as he intends to rewrite history. The utopian fact seems to be projected to another time, although soon we verify that such a projection implies a block. Thus, in the article the dimensions of the idea of history are discussed, as a plot and as a writing of the future, with its own language and its own internal determinations. Such idea of history finds its limitation with the horizon of the future where the communication of writing is received.